Measurement of Natural Radioactivity Level in Selected Phosphate Fertilizer Samples Collected from Iraqi Markets - S. Khalf, Yassamin; K. Mohammad, Kareem (Al-Nahrain Journal of Science, 2021)
The Gamma-ray spectrometry (spectra line Gp) and a high-purity germanium (HPGe) detector were used to determine the activity concentrations of 226Ra, 232Th, and 40K in fertilizer samples. 226Ra, 232Th, and 40K activity concentrations in fertilizers and phosphate raw. In this study the gamma index (Ig), Radium equivalent dose (Raeq), dose rate (DR), external hazard index (Hex) internal hazard index (Hin), annual effective dose outdoor (AEDout) and annual effective dose indoor (AEDin) were found. This study could serve as a starting point for figuring out how fertilizer radiation affects human health.